Convergence in Spanish provinces - Antonio Montanes; Lorena Olmos; Marcelo Reyes (European Regional Science Association (ERSA), 2015)
This paper analyses to what extent the Spanish provinces have shown a convergence process since 1980 to nowadays. The application of the Phillips-Sul methodology to the HDI recently developped by IVIE lead us to show that we cannot admit the exitence of a unique convergence process between them. Rather, we can observe the exis- tence of dierentiated clubs up to 2007. Higher school education and creativity plays determinant roles in explaining the evolution of these clubs. Im- provements in these variables are vital for the provinces to move to the clubs with highest HDI values.
Keywords: C22; E43; 330; convergence; clubs; education; Human development Index